Incidence Of Anxiety And Depression Among Patients Undergoing Hemodialysis In A Tertiary Care Hospital (Journal of Pharmaceutical Negative Results, 2023)
Chronic kidney disease is defined as kidney damage for more than 3 months, as defined by structural and functional abnormalities of the kidney with or without decreased GFR, manifested by either, Pathological abnormalities; or makers of kidney damage, including abnormalities in the composition of the blood or urine, abnormalities in imaging testing. GFR < 60ml/min/1.73 m2 for > 3 months, with or without kidney damage is also described as CKD Anxiety is an emotion characterized by feelings of tension, worried thoughts and physical changes like increased blood pressure.